ENTERPRISES IN COMPETITIVENESS FINANCIAL RISK IMPORTANCE (Journal of Multidisciplinary Sciences and Innovations, 2025)
Long term in the period competitiveness support and increase necessary condition of the enterprise next to develop aimed at active position , that with together progressive development process with related risks control to do and to manage is to provide .